PENTINGNYA PENDIDIKAN MORAL DALAM PENDIDIKAN KEWARGANEGARAAN - Sendi Fauzi Giwangsa (Latifah Pres, 2018)
The recent phenomenon of moral decline has become a concern for some of our people. This is marked by the many immoral behaviors that are widely reported by national television. Education is one of the tools in instilling morals in children. Both education in the family environment and formal education at school. Citizenship Education (PKn) is one of the subjects that aims to encourage morale in students. Naum in practice often learning PKn only teaches knowledge only without any more emphasis on aspects of attitude and skills. Knowledge is important because knowledge will be the basis for action. But that is not enough to instill moral in students. Strengthening is needed especially in the aspect of attitude and of course it must be practiced in everyday life so that because morals are not enough just for material knowledge but also a habit of behaving in life.